FILOSOFI RIDEO ERGO SUM: MEMAKNAI MANUSIA SEBAGAI MAKHLUK YANG TERTAWA (HOMO RIDENS) - Siswadi, Gede Agus; Puspadewi, I Dewa Ayu (Widya Katambung, 2024)
The phrase rideo ergo sum or I laugh because I exist is a philosophy that has a very deep meaning. This is because only humans are able to laugh or are referred to as homo ridens while animals cannot. Although there are animal sounds that resemble laughter, they are not a form of laughter like in humans. Laughter is not a form of meaningless expression. Many things can be obtained by interpreting humans as homo ridens. This research uses library research method with Miles and Huberman analysis pattern. The results in this study are 1). Laughter is a form of authenticity from humans, humans need humor and laughter as an expression of the happiness they experience, humans are unique because humans are able to laugh (homo ridens) as their characteristic. 2). Laughter has a philosophy, because laughing is a form of freedom of expression, and laughter is a form of reality of human freedom. 3). Various things are obtained by humans as homo ridens, especially in the health, so that laughing yoga is a form of actualization of the homo ridens.